A coordination game model of charitable giving and seed money effect - Kentaro Hatsumi (Osaka University, Institute of Social and Economic Research (ISER), 2009)
If potential donors for a charity project possess the warm-glow properties in their preferences, we can represent their behavior with a coordination game. Accordingly, we construct a simultaneous incomplete information game model of charitable giving based on a simple global coordination game. We demonstrate that merely by the effect of seed money to shift the threshold requirement of the donations for project success downwards, the proportion of donors and the total amount of donations strictly and continuously increase with the amount of seed money. This result is compatible with the field experimental evidence in List and Lucking-Reiley [List, J. A., Lucking-Reiley, D., 2002. The Effects of Seed Money and Refunds on Charitable Giving: Experimental Evidence from a University Capital Campaign. Journal of Political Economy 110 (1), 215-233].
Keywords: C72; D82; H41; L31; 330; charity; seed money; global game; coordination game; excludable threshold public good